Environmental Taxes: Challenges and Opportunities for Sustainable Development - Ahmad Firdaus; Abdul Wahab; Lina Mariana; Munifa Munifa (Universitas Muhammadiyah Makassar, 2024)
This study explores the role of environmental taxes as a critical instrument for sustainable development, focusing on both the challenges and opportunities presented by their implementation in Indonesia. Environmental taxes, often termed